A Comparative case study of the Philippine Daily Inquirer Employee's Union (PDIEU) and the Manila Times Metromedia Employee's Union (MTMEU) - Cruz, John Vincent S.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 1999)
It is the purpose of this study to determine, contrast and compare the nature and dynamics of two media unions existing in the two national daily newspapers which have been known for their relatively progressive stance. The labor-management relations, principles, objectives, structures, problems, and prospects of the Philippine Daily Inquirer Employees' Union and the Metro Times Employees' Union were tackled and analyzed in order to determine the role each plays in the better management of their respective newspapers. A short historical background of the two unions was also included in order to contextualize each union's formation. In the end the two unions were evaluated on the merits of the available data, and conclusions derived on the role that these unions played in the daily operations of both the Philippine Daily Inquirer and the Manila Times.
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman
Keywords: Philippine Daily Inquirer Employee's Union (PDIEU) -- Philippines -- Labor union democracy; Manila Times Metromedia Employee's Union (MTMEU) -- Philippines -- Labor union democracy